Preparation method of laser-induced flexible electrochromic electrode and flexible electrochromic device

By electrochemically reducing the Sn metal layer on a conductive ITO substrate and reacting it with tungstic acid sol, combined with laser annealing, a low-cost, highly conductive and patternable flexible WO3 electrode was prepared, solving the high preparation cost and patterning problems in the existing technology.

CN120779635APending Publication Date: 2025-10-14HENAN UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511194293.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-25
Publication Date
2025-10-14

AI Technical Summary

Technical Problem

In the existing technology, the magnetron sputtering method for preparing flexible WO3 electrodes is costly, the coating method affects the conductivity of the electrode, and it is difficult to achieve patterned design.

Method used

A laser-induced method is used to form a Sn metal layer on a conductive ITO flexible substrate through electrochemical reduction, which is then reacted with tungstic acid sol to generate a WO3 precursor film. Laser annealing is used to complete heating annealing in the near-surface layer to form a WO3 flexible electrochromic film, achieving good contact with the substrate and patterned design.

Benefits of technology

The low-cost preparation of flexible WO3 electrodes was achieved, which maintained good conductivity and enabled patterned design, making them suitable for the production of flexible electrochromic devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120779635A_ABST
    Figure CN120779635A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of flexible electrochromic devices, and particularly relates to a preparation method of a laser-induced flexible electrochromic electrode and a flexible electrochromic device. Metal Sn particles are obtained on the surface of a conductive ITO substrate through electrochemical reduction, then the metal Sn particles and tungstic acid sol are mixed and react to form a WO3 precursor thin film (HxWO3 thin film), and the thin film is in good contact with a substrate layer; according to laser annealing, heating annealing can be completed on a near-surface layer by controlling laser energy and the thickness of a heating layer, a substrate layer and an ITO conducting layer are not affected, and in-situ converted WO3 can be firmly attached to the conducting substrate. According to the method, the flexible WO3 electrode can be rapidly and efficiently obtained at normal temperature and normal pressure, compared with a magnetron sputtering method, the production cost is low, and the problem that the conductivity of the electrode is affected by a coating method cannot occur due to the fact that no other binder component is used.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of flexible electrochromic devices, and particularly relates to a preparation method of a laser-induced flexible electrochromic electrode and a flexible electrochromic device. BACKGROUND

[0002] Flexible electronic devices have the characteristics of light weight, bendability, strong adhesion, and good conformability, and have broad application environment in the fields of artificial intelligence, medical detection, wearable technology, etc. Electrochromic devices can change the color, depth, and light transmittance of the device by voltage adjustment, and thus have wide application in energy saving and environmental protection, display, etc.

[0003] A flexible electrochromic device is disclosed in Chinese Patent No. CN104932169B, which was granted on August 25, 2017, and has the publication number CN104932169B. The flexible electrochromic device includes a working electrode, a counter electrode, and an electrolyte layer. The working electrode is a transparent and fast-response flexible electrochromic film. The counter electrode is PET-ITO. The electrolyte layer is between the working electrode and the counter electrode. The edge of the flexible electrochromic device is packaged with resin. The flexible electrochromic film is a mixed electrochromic material composed of H2WO4·H2O and poly 3,4-ethylenedioxythiophene (PEDOT). In the production process, an Ag layer is first deposited on a flexible substrate using a magnetron sputtering method, then a mixed solution of H2WO4·H2O and PEDOT is prepared, and finally a flexible electrochromic film is prepared through repeated pulling, heat sealing, and other processes. The overall production process is complicated, and the feasibility of industrial implementation is not high.

[0004] WO3 is a classic electrochromic material, which has the characteristics of fast response, large light transmittance adjustment range, and good cycle stability, and is commonly used in hard devices with conductive glass as the substrate. However, its growth usually needs to go through a high-temperature annealing process above 400℃, which cannot be tolerated by the commonly used organic flexible substrate.

[0005] The commonly used method for producing flexible WO3 electrodes is magnetron sputtering coating, but the production cost is high, which restricts the large-scale promotion of WO3-based flexible electrochromic devices. Another commonly used method is to mix the prepared WO3 powder with a binder to prepare a slurry, and then coat it on a flexible conductive substrate. This method not only increases the coating and drying process, but also seriously affects the conductivity of the electrode due to the addition of the binder, which leads to poor contact between the material and the substrate and affects the performance of the device. Therefore, the preparation of flexible WO3 electrodes is still a challenge. SUMMARY

[0006] The application aims to provide a preparation method of a laser-induced flexible electrochromic electrode, and solve the problems of high production cost and influence of coating method on electrode conductivity in the prior art of preparing a flexible WO3 electrode by a magnetron sputtering method.

[0007] The second object of the application is to provide a flexible electrochromic device using the flexible electrochromic electrode prepared by the above method, and solve the problems of high production cost and difficulty in achieving a patterned design in the prior art of a flexible electrochromic device.

[0008] In order to achieve the above object, the technical scheme adopted by the application is as follows:

[0009] A preparation method of a laser-induced flexible electrochromic electrode, comprising the following steps:

[0010] (1) electrochemically reducing a conductive ITO flexible substrate to form a Sn metal layer on the surface of the conductive ITO flexible substrate;

[0011] (2) mixing and reacting the Sn metal layer of the conductive ITO flexible substrate and tungstic acid sol to form a WO3 precursor film;

[0012] (3) laser annealing the WO3 precursor film to form a WO3 flexible electrochromic film in situ.

[0013] The application belongs to an improved application, and first obtains metal Sn particles on the surface of a conductive ITO substrate by electrochemical reduction, and then mixes and reacts with tungstic acid sol to form a WO3 precursor film (H x WO3 film), and the film has good contact with the substrate layer; laser annealing can complete heating annealing in a near-surface layer by controlling laser energy and heating layer thickness, without affecting the substrate layer and the ITO conductive layer, and the in-situ converted WO3 can be firmly attached to the conductive substrate. The method can quickly and efficiently obtain a flexible WO3 electrode at normal temperature and pressure, and has low production cost compared with the magnetron sputtering method, and also does not have the problem of influence of the coating method on the conductivity of the electrode due to the absence of other adhesive components.

[0014] Preferably, the wavelength of the laser annealing in step (3) is 1064 nm, and the power is 0.05-0.2 W. Further preferably, the laser annealing is selective annealing according to a design pattern, and the unannealed part is stripped after annealing to form a patterned electrode. This patterning method can also overcome the deficiency that the mask pattern must have continuity in the current chemical etching method.

[0015] Preferably, the working solution used in the electrochemical reduction in step (1) is a KOH solution, the voltage is constant at 3.5-6.0 V, and the time is 10-40 s. Further preferably, the concentration of the KOH solution is 0.1-0.2 mol / L.

[0016] Preferably, the concentration of tungstic acid sol in terms of W is 0.1-0.2 mol / L. Further preferably, the preparation of the tungstic acid sol comprises mixing sodium tungstate solution and hydrochloric acid, then adding oxalic acid to mix until the solution becomes transparent, and then adding water and KCl to mix and age. More preferably, hydrochloric acid is added to a pH of 0.9-1.2. For example, the pH is 1.

[0017] Preferably, the conductive ITO flexible substrate comprises a PET flexible substrate and a conductive ITO layer compounded on the PET flexible substrate.

[0018] A flexible electrochromic device using the flexible electrochromic electrode prepared by the above preparation method.

[0019] Based on the above flexible electrochromic electrode, a flexible electrochromic device can be assembled according to existing methods, which has modulation effect on visible light in different voltage ranges, can be designed in patterns, and has the characteristics of low production cost, suitability for patterning, and good electrochromic performance. BRIEF DESCRIPTION OF DRAWINGS

[0020] Figure 1 SEM images during the preparation of the electrode of Example 1 of the present application: a) after electrochemical reduction; b) after tungstic acid reaction; c) after laser annealing; d) after 1500 times of bending;

[0021] Figure 2 Physical photos of the electrode before (left) and after (right) annealing in Example 1 of the present application;

[0022] Figure 3 Bending diagram of the WO3 / ITO / PET flexible electrode of Example 1 of the present application;

[0023] Figure 4 Transmittance change diagram of the WO3 / ITO / PET flexible electrode in different modulation voltage ranges in the experimental example of the present application;

[0024] Figure 5 Physical photo of the peony pattern electrode after color change in Experimental Example 1 of the present application. DETAILED DESCRIPTION

[0025] (I) Preferred embodiment description of the preparation method of the laser-induced flexible electrochromic electrode of the present application and the flexible electrochromic device

[0026] The technical concept of the present application is to generate WO3 precursor in situ on the conductive ITO substrate, and then to realize near-surface layer annealing by adjusting laser energy and heating layer thickness, so as to form WO3 in situ without affecting the substrate layer and ITO conductive layer, realize good combination of WO3 and conductive substrate, and design the flexible electrode in a pattern.

[0027] Specifically, the in-situ generation of WO3 precursor on the conductive ITO substrate is to electrochemically reduce the Sn metal layer on the conductive ITO substrate, and then react with tungstic acid sol to realize the in-situ generation of WO3 precursor on the conductive substrate.

[0028] The electrochemical reduction is carried out in a KOH solution, and the conductive surfaces of two ITO (indium tin oxide) / PET (polyethylene terephthalate) are oppositely immersed in the KOH solution, and a constant voltage is applied to the conductive substrate by an electrochemical workstation. The conductive ITO surface of ITO / PET grows a grayish-brown Sn metal layer under the action of electrochemical reduction. In this process, the controllable voltage is 3.5-6.0V, and the reaction time is 10-40s.

[0029] The tungstic acid sol can be prepared according to the prior art. For example, sodium tungstate dihydrate solution and hydrochloric acid are subjected to acidification reaction until the solution turns yellow, then oxalic acid is added to mix until the solution becomes transparent, and then water is added for dilution, and then KCl is added to stir the sol and then aged to obtain a stable tungstic acid sol.

[0030] For each 0.01 mole of sodium tungstate dihydrate, 50-80mL of water is added to stir and mix to prepare a sodium tungstate dihydrate solution, 3-5mol / L of hydrochloric acid solution is added dropwise until the pH of the system is 0.9-1.2, then 0.9-1.5g of oxalic acid is added for mixing, 50-80mL of water is added for dilution, then 1-2g of KCl is added to promote ion stability, and the aging time is more than 24h.

[0031] The above tungstic acid sol is added dropwise to the metal layer of the flexible substrate, and the grayish-brown metal layer quickly turns blue. After the reaction of the metal layer is completed, a uniform blue film is formed.

[0032] During laser annealing, the laser power is adjusted to 0.05-0.2W (more preferably 0.1-0.2W), the laser wavelength is 1064nm, the blue tungsten acid / ITO / PET electrode is irradiated with laser, and the film after irradiation turns white, i.e. a patterned WO3 / ITO / PET electrode is obtained. During laser annealing, the designed pattern can be input into the laser processing machine to realize the patterned processing of the electrode. The adhesion of the part not subjected to laser treatment is low, which can be removed from the conductive substrate by water washing treatment to obtain a patterned electrode without damaging the substrate layer.

[0033] The preferred embodiments of the present application will be illustrated below with specific examples. In the following examples, the raw materials used are all commercially available conventional raw materials, and the processing methods used are all conventional methods, unless otherwise specified.

[0034] Example 1

[0035] The preparation method of the laser-induced flexible electrochromic electrode of the present embodiment adopts the following steps:

[0036] S1. Preparation of tungstic acid sol

[0037] 3.3g of Na2WO4·2H2O was weighed with an electronic balance and added to 50ml of deionized water under magnetic stirring. 3M HCl was added dropwise, and when the pH dropped to 0.95, a slight yellowing of the solution was observed, at which point the addition of hydrochloric acid was stopped. 0.9g of oxalic acid powder was added to the solution, stirred for 30 minutes, and the solution became transparent. 50ml of deionized water was added to the solution for dilution, 1g of KCl was added, stirred until completely dissolved, and aged for 24 hours to obtain a stable tungstic acid sol.

[0038] S2. Preparation of tungstic acid electrode

[0039] A 0.2mol / L KOH solution of 50mL was prepared, and two pieces of 2cm×3.5cm ITO / PET conductive surface were immersed in the KOH solution. An electrochemical workstation was used to apply a constant voltage to the conductive substrate, with a voltage of 3.5V and a reaction time of 40s, and a grayish-brown metal layer was grown on the negative electrode piece.

[0040] The tungstic acid sol was evenly dropped on the Sn metal layer, and the grayish-brown metal layer quickly turned blue. After the metal layer was completely reacted (the reaction was relatively rapid, and the time was generally a few seconds to a few minutes, and the color did not change), the blue liquid was poured off, the surface residual liquid was absorbed with a water-absorbing paper, and the conductive substrate was washed slowly from top to bottom with deionized water. A uniform blue film (i.e. blue tungstic acid / ITO / PET electrode) could be observed on the conductive substrate.

[0041] The tungstic acid solution added here is in excess, and in other implementation scenarios, the electrode after electrochemical reduction can also be directly inserted into the tungstic acid solution until the reaction is complete.

[0042] S3. Preparation of WO3 / ITO / PET patterned flexible electrode

[0043] The designed pattern was input into the laser processing machine, the laser power was adjusted, and the blue tungstic acid / ITO / PET electrode was irradiated with laser. The film after irradiation turned white, and then the un-laser-treated part was peeled off by water washing, thereby obtaining the patterned WO3 / ITO / PET electrode. The wavelength of the laser used here was 1064nm, and the power was 0.2W.

[0044] Example 2

[0045] The preparation method of the laser-induced flexible electrochromic electrode of this example adopts the following steps:

[0046] S1. Preparation of tungstic acid sol

[0047] Take 3.3g Na2WO4·2H2O with an electronic balance, and add 50ml deionized water under magnetic stirring. Add 3M HC1 drop by drop, and stop adding hydrochloric acid when the pH drops to 0.95. At this time, a slight yellowing of the solution is observed. Add 0.9g of oxalic acid powder to the solution, stir for 30 minutes, and the solution becomes transparent. Dilute with 50ml deionized water, add 1g KCl, stir until completely dissolved, and let stand for 24 hours to obtain a stable tungstic acid sol.

[0048] S2. Preparation of tungstic acid electrode

[0049] Prepare 50mL of 0.2moI / L KOH solution, and immerse the conductive surfaces of two pieces of 2cm x 3.5cm ITO / PET facing each other in the KOH solution. Apply a constant voltage to the conductive substrate using an electrochemical workstation, set the voltage to 6V, and the reaction time to 10s, and a grayish-brown metal layer is grown on the negative electrode piece.

[0050] Drop the tungstic acid sol evenly on the Sn metal layer, and the grayish-brown metal layer quickly turns blue. After the metal layer is completely reacted, pour off the blue liquid, use a water-absorbing paper to absorb the residual liquid on the surface, and slowly rinse from top to bottom with deionized water. A uniform blue film (i.e. blue tungstic acid / ITO / PET electrode) can be observed on the conductive substrate.

[0051] S3. Preparation of WO3 / ITO / PET patterned flexible electrode

[0052] Input the designed pattern into the laser processing machine, adjust the laser power, and irradiate the blue tungstic acid / ITO / PET electrode with the laser. The film after irradiation turns white, and then the unprocessed part is peeled off by water washing, and a patterned WO3 / ITO / PET electrode is obtained. The laser wavelength used here is 1064nm, and the power is 0.2W.

[0053] Example 3

[0054] The preparation method of the laser-induced flexible electrochromic electrode of this example adopts the following steps:

[0055] S1. Preparation of tungstic acid sol

[0056] Weigh 3.3 g of Na2WO4·2H2O with an electronic balance, and add 50 ml of deionized water under magnetic stirring. Add 3M HCl drop by drop, and stop adding HCl when the pH drops to 1.2. At this time, a slight yellowing of the solution is observed. Add 0.9 g of oxalic acid powder to the solution, stir for 30 minutes, and the solution becomes transparent. Dilute the solution by adding 50 ml of deionized water, add 1 g of KCl, stir until completely dissolved, and let stand for 24 hours to obtain a stable tungstic acid sol.

[0057] S2. Preparation of tungstic acid electrode

[0058] Prepare 50 mL of 0.2 mol / L KOH solution, and immerse two pieces of ITO / PET conductive surface opposite each other in the KOH solution. Apply a constant voltage to the conductive substrate using an electrochemical workstation, set the voltage to 3.5 V, and the reaction time to 40 s. A grayish-brown metal layer is grown on the negative electrode piece.

[0059] Drop the tungstic acid sol evenly on the Sn metal layer, and the grayish-brown metal layer quickly turns blue. After the metal layer is completely reacted, pour away the blue liquid, use a water-absorbing paper to absorb the residual liquid on the surface, and slowly rinse from top to bottom with deionized water. A uniform blue film (i.e., a blue tungstic acid / ITO / PET electrode) can be observed on the conductive substrate.

[0060] S3. Preparation of WO3 / ITO / PET patterned flexible electrode

[0061] Input the designed pattern into the laser processing machine, adjust the laser power, and irradiate the blue tungstic acid / ITO / PET electrode with the laser. The film after irradiation turns white, and then the unprocessed part is peeled off by water washing, thereby obtaining a patterned WO3 / ITO / PET electrode. The wavelength of the laser used here is 1064 nm, and the power is 0.2 W.

[0062] Example 4

[0063] The preparation method of the laser-induced flexible electrochromic electrode of this example uses the following steps:

[0064] S1. Preparation of tungstic acid sol

[0065] Weigh 3.3 g of Na2WO4·2H2O with an electronic balance, and add 50 ml of deionized water under magnetic stirring. Add 3M HCl drop by drop, and stop adding HCl when the pH drops to 0.95. At this time, a slight yellowing of the solution is observed. Add 0.9 g of oxalic acid powder to the solution, stir for 30 minutes, and the solution becomes transparent. Dilute the solution by adding 50 ml of deionized water, add 1 g of KCl, stir until completely dissolved, and let stand for 24 hours to obtain a stable tungstic acid sol.

[0066] S2. Preparation of tungstic acid electrode

[0067] A 0.2 mol / L KOH solution of 50 mL was prepared, and two pieces of 2 cm x 3.5 cm ITO / PET conductive surfaces were oppositely immersed in the KOH solution. A constant voltage was applied to the conductive substrate by an electrochemical workstation, and the voltage was set to 3.5 V. The reaction time was 40 s, and a grayish-brown metal layer was grown on the negative electrode piece.

[0068] A tungsten acid sol was uniformly dropped on the Sn metal layer, and the grayish-brown metal layer quickly turned blue. After the metal layer was completely reacted, the blue liquid was poured out, the surface residual liquid was absorbed with a water-absorbing paper, and the conductive substrate was slowly washed from top to bottom with deionized water. A uniform blue film (i.e., a blue tungsten acid / ITO / PET electrode) was observed on the conductive substrate.

[0069] S3. Preparation of a patterned WO3 / ITO / PET flexible electrode

[0070] A designed pattern was input into a laser processing machine, and the laser power was adjusted. The blue tungsten acid / ITO / PET electrode was irradiated with a laser, and the irradiated film turned white. After washing with water, the part not treated with a laser was peeled off, and a patterned WO3 / ITO / PET electrode was obtained. The wavelength of the laser used here was 1064 nm, and the power was 0.1 W.

[0071] Example 5

[0072] The flexible electrochromic device of this example used the flexible electrochromic electrode obtained in Example 1, and the assembly process is described as follows: The tungsten trioxide electrode (2*3.5 cm) prepared in Example 1 was oppositely placed with a flexible Pt / PET electrode of the same size with a pinhole, and a back-shaped heat-sealing film was used to separate them. The pinhole of the Pt electrode was located in the middle of the cavity formed by the back-shaped heat-sealing film. The electrodes were heated until the heat-sealing film melted and deformed, and the two electrodes were firmly bonded. Then, the electrolyte was injected into the cavity between the two electrodes by vacuum suction injection. Finally, another piece of heat-sealing film was used to seal the pinhole on the Pt electrode side. The electrode liquid used here was 1 mol / L LiClO4 / PC (propylene carbonate).

[0073] (II) Experimental Examples

[0074] Experimental Example 1

[0075] The patterned flexible electrode obtained in Example 1 was characterized, and the results are shown in Figure 1 .

[0076] As can be seen from the SEM image of Figure 1 , a large number of particles appeared on the surface of the ITO / PET electrode after electrochemical reduction, which were Sn elemental particles Figure 1a); After reacting with tungstic acid, the surface becomes flat and smooth ( Figure 1 b); After laser annealing treatment, a uniform film appears with obvious and abundant pore structures on the surface ( Figure 1 c); After 1500 bending cycles, the electrode surface has hardly changed ( Figure 1 d).

[0077] The above results show that after a series of treatments, a porous thin film electrode is generated on the surface layer. The electrode is very strong and can withstand 1,500 bends without obvious changes, making it suitable for use as a flexible electrode.

[0078] In Example 1, the actual photos of the electrodes before and after laser annealing are as follows: Figure 2 As shown, the WO3 precursor before annealing is a blue film, which is converted into a white film after laser annealing. Figure 2 In the figure, HAUST is the printed LOGO icon of Henan University of Science and Technology. The image can still be clearly seen through the electrode, indicating that the electrode has good light transmittance and can be used as a transparent device.

[0079] In Example 1, the bending diagram of the prepared WO3 / ITO / PET flexible electrode is as follows Figure 3 The electrode exhibits good flexibility, and its structure remains intact after repeated bending.

[0080] Experimental Example 2

[0081] The WO3 / ITO / PET flexible electrode obtained in Example 1 was used as the working electrode, Pt as the counter electrode, and a 1 mol / L lithium perchlorate (LiClO4) propylene carbonate (PC) solution as the electrolyte. A full spectrum response test of visible light was performed. Modulation voltage was applied in different voltage ranges, and the light transmittance at 670 nm was tested. The results are shown in FIG. Figure 4 shown.

[0082] Depend on Figure 4 It can be seen that the WO3 / ITO / PET flexible electrode of Example 1 has a modulation effect on visible light and can be used as an electrochromic electrode.

[0083] The WO3 / ITO / PET flexible electrode of Example 1 was processed into a peony pattern. Figure 5 The photo shows the color change of the peony pattern electrode, which shows that this method has unique advantages in processing patterned flexible electrochromic electrodes.

[0084] The effects of the flexible electrochromic electrodes prepared in Examples 2-4 above are basically the same as those in Example 1.

[0085] Finally, it should be noted that the above only describes the preferred embodiments of the present application and is not intended to limit the present application. Although the present application has been described in detail with reference to the foregoing embodiments, those skilled in the art will appreciate that the technical solutions described in the foregoing embodiments can be modified or some technical features thereof can be replaced by equivalent features, and any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing a laser-induced flexible electrochromic electrode, characterized in that: The following steps are involved: (1) electrochemically reducing a conductive ITO flexible substrate to form a Sn metal layer on the surface of the conductive ITO flexible substrate; (2) The Sn metal layer of the conductive ITO flexible substrate reacts with the tungstic acid sol to form a WO3 precursor film; (3) The WO3 precursor film is laser annealed to form a WO3 flexible electrochromic film in situ.

2. The method for preparing a laser-induced flexible electrochromic electrode according to claim 1, wherein: The wavelength of the laser annealing in step (3) is 1064 nm, and the power is 0.05-0.2 W.

3. The method for preparing a laser-induced flexible electrochromic electrode according to claim 2, wherein: The laser annealing is a selective annealing performed according to a design pattern. After annealing, the unannealed portion is peeled off to form a patterned electrode.

4. The method for preparing a laser-induced flexible electrochromic electrode according to claim 1, wherein: The working fluid used for the electrochemical reduction in step (1) is KOH solution, the voltage is constant at 3.5-6.0V, and the time is 10-40s.

5. The method for preparing a laser-induced flexible electrochromic electrode according to claim 4, wherein: The concentration of the KOH solution is 0.1-0.2 mol / L.

6. The method for preparing a laser-induced flexible electrochromic electrode according to claim 1, wherein: The concentration of the tungstate sol in terms of W is 0.1-0.2 mol / L.

7. The method for preparing a laser-induced flexible electrochromic electrode according to claim 6, wherein: The preparation of the tungstate sol includes: mixing a sodium tungstate solution and hydrochloric acid for reaction, then adding oxalic acid and mixing until the solution becomes transparent, then adding water and KCl and mixing and aging.

8. The method for preparing a laser-induced flexible electrochromic electrode according to claim 7, wherein: Add hydrochloric acid until the pH is between 0.9-1.

2.

9. The method for preparing a laser-induced flexible electrochromic electrode according to claim 1, wherein: The conductive ITO flexible substrate comprises a PET flexible substrate and a conductive ITO layer composited on the PET flexible substrate.

10. A flexible electrochromic device using the flexible electrochromic electrode obtained by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • A fast-response flexible electrochromic device and its application

    CN104932169B